ET-traps as a potential treatment for COVID-19 - Arjun Jain; Vidhi Mehrotra (Elsevier, 2020)
The ET-traps are Fc-fusion proteins that have shown a therapeutic potential in the diabetes disease space. Previous studies have also discussed the potential use of ET-traps for other diseases, including HIV / AIDS. These diseases are all associated with pathologically elevated endothelin −1 (ET-1) levels. This paper discusses the potential use of ET-traps for the COVID-19 pandemic, which previous studies have shown involves high cytokine levels. Research has also shown that ET-1 is a stimulus for the induction of these pro-inflammatory cytokines. Hence, the ET-traps would likely be effective in patients suffering from COVID-19. If successful at the preclinical and clinical testing, the ET- traps would provide a much-awaited therapy.